By His Excellency Thomas Chittenden, Esquire ... A proclamation : ... to appoint Thursday the twenty fifth day of November next, to be observed as a day of public thanksgiving and praise throughout this state ... Given under my hand in Council chamber in Castleton this 20th day of October, A.D. 1790 . (1790)
October 20, 1790 Proclamation of Governor Thomas Chittenden establishing November 25th as a day of public thanksgiving and praise in the state for God's merciful and gracious bounties.